Analysis of Oxygen Absorption at 60 GHz Frequency Band - (:unkn) unknown (IEEE, 2019)
In this paper, analysis of atmospheric attenuation due to oxygen absorption of 60 GHz band signals is presented. The analysis is based on a time-domain simulation model that incorporates medium dispersion properties. For this purpose, a multi-pole material dispersion model of oxygen absorption is developed based on available experimental data. The simulation algorithm is based on the auxiliary differential equation (ADE) finite difference time domain (FDTD) technique which implements the general polarization formulation and uses the rotating boundary conditions to allow for long propagation distances. The results are useful in the prediction of propagation power loss such that methods for compensation can be devised.
Keywords: atmospheric attenuation; 5G communications; FDTD method; Lorentz model; oxygen absorption